Analysis of Non-Conformity of Space Utilization in the Corridor of the Deli River Basin in Medan City - Rayendra Gunawan Nasution; Abdiyanto; Cut Nuraini; Wahyu Hidayat (Yayasan Multidimensi Kreatif, 2024)
Increased population growth causes land needs to increase and forces underprivileged people to live in inappropriate areas such as river banks. The purpose of this research is to identify the types of spatial utilization and the dynamics of spatial utilization of non-conformity to spatial planning regulations in the Deli River border corridor in Medan City. This research uses a descriptive-qualitative approach with Geographic Information System (GIS)-based spatial analysis method, particularly overlay technique, to compare the regulation of Medan City Regional Regulation on Regional Spatial Plan Year 2022-2042. The analysis in 2024 showed significant discrepancies between the existing space utilization and the planned spatial pattern of the RTRW, indicating deviations between planning and actual conditions that may affect ecological and economic functions and hinder sustainable development. The identification of mismatches in various areas shows that incompatible land uses can disrupt the balance of the ecosystem and require more effective spatial adjustments.